Supporting self-regulated learners with formative assessments using automatically created QTIQuestions - AL-Smadi, M.; Guetl, Christian (Curran Associates, 2011)
Recently, a new age of information has appeared where information and communication technology plays a major role in education and learning society. Consequently, modern learning settings represented by emerging learning strategies have been used in higher education. A primary goal for higher education is to support students and lifelong learners to be independent, self-motivated, and self-regulated. As a result, students should be provided with enhanced approaches of learning and assessment that support them to set their learning goals effectively, to plan and use effective strategies in order to achieve their goals, to manage resources, to monitor their understanding, and to assess their progress towards their goals. This paper proposes an enhanced approach of e-assessmentwhere automatically created formative assessments are provided to support self-regulated learners.